The Present Situation - David Buege; Marlon Blackwell (Oz, 2015)
The best-known building in northwest Arkansas and the most highly and widely acclaimed is a modest chapel in the pleasant if somewhat prosaic setting of a scruffy, even more modest Ozark forest near Eureka Springs.